Pengaruh Kualitas Makanan, Cita Rasa Dan Persepsi Harga Terhadap Loyalitas Konsumen Di Rumah Makan Sutini Simbarwaringin Lampung Tengah - Yateno; Selamet Fuadi; Tyas Giri Anjani (Jurnal Manajemen DIVERSIFIKASI, 2024)
The aim of this research is to determine the influence of food quality, taste and priceperception on consumer loyalty at Ibu Sutini Restaurant. The research method usesquantitative research. The objects in the research are food quality, taste, price perceptionand consumer loyalty at Ibu Sutini's Restaurant. The population in this study is all consumerswho visit restaurants. Samples were taken using an accidental sampling technique thathappened to be encountered during the research. The number of samples was 66 consumers.Data was taken using a closed questionnaire on a 1-5 Likert scale which was then analyzedusing multiple linear regression techniques with the help of SPSS version 21.0. The researchresults show that the food quality variable influences consumer loyalty, the taste variableinfluences food loyalty, the price perception variable has a positive influence on consumerloyalty, and the food quality, taste and price perception variables simultaneously influenceconsumer loyalty. Thus, it can be concluded that the variables of food quality, taste and priceperception can increase consumer loyalty to Ibu Sutini's Restaurant.